AKTIVITAS WISATA SPIRITUAL DAN MOTIVASI BERWISATA DI DAYA TARIK WISATA TANAH LOT KABUPATEN TABANAN - Kusuma, I Gusti Agung Riza Dwi; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 4 No 2 (2016): VOL 4, NO 2 (2016): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2016)
Research on the factors that motivate tourists visiting Tourist Attraction Tanah Lot, who lifted the title "Spiritual Tourism Activity and Motivation Traveled in Tourist Attractions Tanah Lot Tabanan Regency” The purposes of this study are to what the motivation a tourist’s visited Tanah Lot. Data collection techniques in this research, by observation, as many as 65 pieces distributing questionnaires to the respondents, and documentation of studies by taking a picture Tourist Attraction in the area of Tanah Lot. The data have been obtained were analyzed using the technique of data tabulation. Tabulation is the process of placing the data in tabular form by making a table that contains data in accordance with the needs analysis. Tables are made should be able to summarize all the data to be analyzed. Results from this research is in addition to be a place for traveling because it has beautiful scenery, Tourist AttractionsTanah Lot also many tourists who make it as a place for Spiritual Tourism activities as the main products in Tanah Lot is building his Temple. From the results of questionnaires distributed at the time of the research results obtained include: Other than for the purpose of fun, tourists who come in large part dominated by their curiosity to get to know the local culture and local wisdom of people want to know, in addition to the tourists there are also very enthusiastic in doing the Spiritual Tourism activities in Tanah Lot, they have a strong interest in conducting Spiritual Tourism, because there are a variety of benefits that we can while doing activities The Spiritual Tourism them feel more calm, comfortable, and peaceful.
Keywords: Motivation, Spiritual Tourism, Traveller, Tanah Lot